Peran Penegakan Hukum Dalam Pembangunan Ekonomi - Sukardi, - (Jurnal Hukum & Pembangunan, 2016)
Economics is the backbone of the people's welfare, and science are the pillars supporting the nation's progress, but the law is the institution that ultimately determine how the public welfare can be enjoyed equitably, as well as how social justice can be realized in people's lives, and how progress of science and technology can bring progress for the people. In essence, the rule of law to support the transformation of SOEs (State-owned enterprises) as a locomotive driver of the national economy, especially in its role of guarding the whole process of public finance management and the area is clean and responsible, and prevent and crack down on leakage and financial irregularities countries in the form of corruption and money laundering, the ultimately boils down to the realization of welfare with social justice for all people.